Deceased donor kidney allocation schemes and international exchange. Issue 1 (February 2020) - Heemann, Uwe; Oberbauer, Rainer; Sprangers, Ben; Gökalp, Cenk; Bemelman, Frederike
Abstract : Purpose of review: In this review, we summarize different allocation schemes around the world and identify ways to exchange organs between countries. Recent findings: The primary goal of transplantation is prolongation of patient survival and an improved quality of life. Most allocation systems try to match the potential survival of the organ with the life expectancy of its recipient. Kidney transplantation enables cost reductions by the avoidance of dialysis for the healthcare system, which is sometimes the driving force for state interventions to enhance donor recruitment The major benefit from international exchange is the possibility to transplant highly sensitized patients or patients with rare HLA allele. In a broad international exchange system, there are three possibilities: exchange of surplus organs, exchange of organs to support patients with a potentially excessive waiting time because of HLA antibodies or rare alleles, and exchange of organs to make the best possible match between donor and recipient. Summary: It is possible to shape a hierarchical allocation scheme, which could be applicable in the majority of populations despite different geographical and socioeconomic conditions: allocation to recipients with special requirements (high-urgency, highly sensitized); identification of a within the region/country; in case no suitable recipient can be identified, offer countrywide or between countries; for every organ transferred to another country, there must be an obligation to give one back.